Pelaksanaan Mediasi Bagi Para Pihak Dalam Perkara Perceraian - Rahmiati Rahmiati; Kairuddin Karim; Auliah Ambarwati (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This research delves into the implementation of divorce case mediation at the Enrekang Religious Court, emphasizing the pre-mediation stages, mediation implementation, and final reporting to the case judge. Findings reveal a structured process involving problem identification, proposal of alternative solutions, and consultation. The mediator is mandated to report mediation outcomes and legal consequences, including a written agreement signed by parties. In cases of agreement, parties present the signed agreement to the judge, potentially leading to a peace decision. The Settlement Agreement, validated by a Deed of Settlement, adheres to court disclosure regulations.